HISTORICAL ASPECT OF THE DEVELOPMENT OF THE PRINCIPLE OF EQUALITY IN LAW - Kopiyka, Kyrylo (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to analyze and summarize research on the content of the concept of the principle of equality and relevant regulatory legal acts and to formulate an author’s definition of the principle of equality in law. Research methods: comparative-analytical, semantic-syntactic, generalization of scientific works and legislative acts, abstraction, etc. Results: the relevance of the development of the categorical-conceptual apparatus for research on the principle of equality in law is substantiated, the essence of the procedure for forming legal concepts is analyzed, and the main scientific approaches to determining the content of the concept of the principle of equality in law are summarized, on the basis of which the corresponding author’s definition is proposed. Discussion: the relevance of defining the conceptual and substantive principles of the principle of equality in law as the main basic aspect of such research has been clarified, the main features of the procedure for forming legal concepts have been analyzed and the most optimal way of such a procedure has been determined, the presence of a significant number of definitions offered by encyclopedic and reference literature, regulatory and legal acts, as well as various scientific studies in the field of jurisprudence has been established. The author concludes that the content of the very concept of the principle of equality and other related concepts is offered by encyclopedic and reference literature, international and national legal acts, and various legal studies, the analysis of which gives rise to the conclusion that legislators and scholars often use the very concept of the principle of equality without detailing its content, or offer definitions which do not fully meet the objectives of our study. The authors of various interpretations of the principle of equality offer their own definitions which do not contain antagonistic contradictions, but have noticeable differences due to their own scientific position, branch of law, and the specifics and purpose of legal research in which this or that interpretation is proposed. The generalization of such scientific positions gives rise to the identification of the leading features of the principle of equality, and their combination in one definition, taking into account the content and use of the general concept of the principle and the content of the definition of “principles” as a specific concept, provides an opportunity to formulate the author’s own definition of the concept of the principle of equality in law.